Infiltration of nickel and copper catalysts into a GDC backbone assisted by supercritical CO2 for efficient SOFC anodes. Issue 7 (16th March 2022) - Guesnet, L.; Aubert, G.; Hubert, S.; Geffroy, P. M.; Aymonier, C.; Bassat, J. M.
Abstract : This study describes an original method developed for the shaping of composite solid oxide fuel cell (SOFC) anodes including either nickel or copper as metal. Abstract : This study describes an original method developed for the shaping of composite solid oxide fuel cell (SOFC) anodes including either nickel or copper as metal. They are prepared by catalyst (nickel or copper nitrates) infiltration into a porous GDC (Ce0.9 Gd0.1 O1.95 ) skeleton. The infiltration by the classical way is compared to the original infiltration by the supercritical way. Therefore, this article details the difference between these two kinds of infiltration and will explain how the infiltration using supercritical CO2 can finally lead to improving the electrochemical performances of the corresponding cells.